Study of Long-term Spectral Evolution and X-Ray and γ-Ray Correlation of Blazars Seen by HAWC - R. Alfaro; C. Alvarez; A. Andrés; J.C. Arteaga-Velázquez; D. Avila Rojas; H.A. Ayala Solares; R. Babu; E. Belmont-Moreno; A. Bernal; K.S. Caballero-Mora; T. Capistrán; A. Carramiñana; et al. (The Astrophysical Journal)
The HAWC Observatory collected 6 yr of extensive data, providing an ideal platform for long-term monitoring of blazars in the very high energy (VHE) band, without bias toward specific flux states. HAWC continuously monitors blazar activity at TeV energies, focusing on sources with a redshift of z ≤ 0.3, based on the Third Fermi-LAT Catalog of High-Energy sources. We specifically focused our analysis on Mrk 421 and Mrk 501, as they are the brightest blazars observed by the HAWC Observatory. With a data set of 2143 days, this work significantly extends the monitoring previously published, which was based on 511 days of observation. By utilizing HAWC data for the VHE γ -ray emission in the 300 GeV–100 TeV energy range, in conjunction with Swift-XRT data for the 0.3–10 keV X-ray emission, we aim to explore potential correlations between these two bands. For Mrk 501, we found evidence of a long-term correlation. Additionally, we identified a period in the light curve where the flux was very low for more than 2 yr. On the other hand, our analysis of Mrk 421 measured a strong linear correlation for quasi-simultaneous observations collected by HAWC and Swift-XRT. This result is consistent with a linear dependence and a multiple-zone synchrotron self-Compton model to explain the X-ray and γ -ray emission. Finally, as suggested by previous findings, we confirm a harder-when-brighter behavior in the spectral evolution of the flux properties for Mrk 421. These findings contribute to the understanding of blazar emissions and their underlying mechanisms.